2016
DOI: 10.1016/j.ihj.2016.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of patients supported by extracorporeal membrane oxygenation for aluminum phosphide poisoning: An observational study

Abstract: Veno-arterial ECMO has been shown to improve the short-term survival of patients with AlP poisoning having severe LV myocardial dysfunction. A low baseline LVEF and longer delay in hospital presentation were found to be predictors of mortality even after ECMO usage. Large, adequately controlled and standardized trials with long-term follow-up must be performed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 20 publications
(24 reference statements)
3
41
0
Order By: Relevance
“…Moreover, Masson et al found a statistically significant survival benefit in ECLS-treated cardiotoxic drugs poisonings as compared to the conventional treatment (7). Mohan and coworkers reached the same conclusions in a comparative analysis of ECLS and standard supportive care in a population of drug intoxications caused by aluminium phosphide (8). Our results are consistent with these previous experiences as ECLS offered a survival to hospital discharge with good neurological recovery of 75%.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Moreover, Masson et al found a statistically significant survival benefit in ECLS-treated cardiotoxic drugs poisonings as compared to the conventional treatment (7). Mohan and coworkers reached the same conclusions in a comparative analysis of ECLS and standard supportive care in a population of drug intoxications caused by aluminium phosphide (8). Our results are consistent with these previous experiences as ECLS offered a survival to hospital discharge with good neurological recovery of 75%.…”
Section: Discussionsupporting
confidence: 89%
“…The small sample size is a limiting factor that could undermine the statistical power of our analysis. However our study population is comparable to that of previous articles of ECLS support for drug intoxication (5)(6)(7)(8). Our conclusions are gathered from a single-center observational experience and may not be representative of the general population.…”
Section: Limitations Of the Studymentioning
confidence: 54%
See 2 more Smart Citations
“…[75] In another study, Mohan et al . [76] indicated that veno-arterial ECMO had a significant role in amelioration of toxicity and improvement of patient survival, principally for high-risk patients. It seems that a swift decision on using ECMO, before considerable reduction in ventricular ejection fraction, is pivotal for a reasonable response.…”
Section: Role Of Extracorporeal Membrane Oxygenation In Patients Suffmentioning
confidence: 99%